2012
DOI: 10.1007/s10157-012-0660-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of IgG deposition in the glomerular mesangial area in patients with IgA nephropathy

Abstract: BackgroundImmunoglobulin (Ig) A nephropathy (IgAN) is characterized by mesangial deposits of IgA1 and C3, often with co-deposits of IgG. We attempted to clarify the clinical significance of mesangial IgG deposition in patients with IgAN.MethodsWe retrospectively reviewed 57 patients who were diagnosed with IgAN on the basis of pathological examination of renal biopsy specimens obtained between October 2006 and December 2010. Subjects were divided into two groups: IgA+IgG deposition (IgA-IgG) group (n = 29) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 18 publications
(21 reference statements)
2
54
2
1
Order By: Relevance
“…11 Recent observational studies have also indicated that the presence of mesangial IgG deposition had clinical significance in IgA nephropathy patients. 13,14 The present study clearly demonstrated that IgA nephropathy patients with glomerular IgG deposition had poorer long-term outcomes and the inclusion of glomerular IgG deposition evaluation in IgA nephropathy provided additional prognostic value in the adjusted model.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…11 Recent observational studies have also indicated that the presence of mesangial IgG deposition had clinical significance in IgA nephropathy patients. 13,14 The present study clearly demonstrated that IgA nephropathy patients with glomerular IgG deposition had poorer long-term outcomes and the inclusion of glomerular IgG deposition evaluation in IgA nephropathy provided additional prognostic value in the adjusted model.…”
Section: Discussionsupporting
confidence: 52%
“…12 Moreover, recent observational studies have suggested that mesangial IgG deposition in IgA nephropathy could be associated with disease severity and renal progression. 13,14 The Oxford-MEST classification of IgA nephropathy identifies four types of lesions as specific pathological features that may act as independent predictors of clinical outcomes: mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental glomerulosclerosis (S), and tubular atrophy/interstitial fibrosis (T). 15,16 However, this new classification does not include immunofluorescence patterns, which might reflect the pathophysiological mechanisms active in IgA nephropathy.…”
mentioning
confidence: 99%
“…15,22 In a Japanese cohort, patients with glomerular IgG deposits had greater proteinuria at presentation and a lower rate of remission of urinary abnormalities after treatment than patients with IgA deposits alone. 23 Complement component 3 (C3) is present in >90% of biopsy samples, but typically C1q (the first subcom ponent of the C1 complex of the classical pathway of complement activation) is absent. The amount of mes angial C3 deposition might be of prognostic value; strong glomerular positivity for C3 on immunofluores cence and low levels of serum C3 were associated with loss of renal function in a report on IgA nephropathy from Korea.…”
Section: Immunohistology Of Iga Nephropathymentioning
confidence: 99%
“…Many surveys of IgAN have been undertaken, with IgAN leading to ESRD in 30-40% of patients within 20 years after diagnosis 22) . In contrast to…”
Section: Discussionmentioning
confidence: 99%